A Short Review on Properties and Applications of Zinc Oxide Based Thin Films and Devices : ZnO as a promising material for applications in electronics, optoelectronics, biomedical and sensors. Issue 2 (1st April 2020) - Vyas, Sumit
Zinc oxide has emerged as an attractive material for various applications in electronics, optoelectronics, biomedical and sensing. The large excitonic binding energy of 60 meV at room temperature as compared to 25 meV of gallium nitride, an III-V compound makes ZnO an efficient light emitter in the ultraviolet (UV) spectral region and hence favourable for optoelectronic applications. The high conductivity and transparency of ZnO makes it important for applications like transparent conducting oxides (TCO) and thin-film transistors (TFT). In this paper, the optoelectronic, electronic and other properties that make ZnO attractive for a variety of applications are discussed. Various applications of ZnO thin film and its devices such as light-emitting diodes (LED), UV sensors, biosensors, photodetectors and TFT that have been described by various research groups are presented.